(untitled) (The Research of Medical Science Review, 2025)
Background: Thymic abnormalities, including thymic hyperplasia and thymoma, are frequently observed in patients with Myasthenia Gravis (MG). Objective: This study aims to evaluate the prevalence of thymic abnormalities in MG patients and explore their correlation with demographic factors, disease severity, and duration. Methods: This cross-sectional study was conducted at the Department of Neurology, Mayo Hospital, Lahore. A total of 136 patients diagnosed with MG were included, based on specific inclusion and exclusion criteria. Thymic abnormalities were diagnosed using imaging techniques. Results: The study found that 50% of the patients had thymic abnormalities, with thymic hyperplasia occurring in 37.1% and thymoma in 12.9%. Thymic abnormalities were more common in older age groups, with 61.8% of patients aged 60–70 years affected. Disease duration was also positively correlated with thymic abnormalities, as 58.2% of patients with more than 5 years of disease had thymic changes. There was a significant correlation between age (p=0.03), disease duration (p=0.01), and MGFA grade (p=0.02) with the presence of thymic abnormalities. However, gender (p=0.56) and comorbidities (p=0.23) showed no significant association. Conclusion: Thymic abnormalities are prevalent in patients with Myasthenia Gravis, particularly in those with longer disease durations and higher disease severity. Age is a significant factor associated with the presence of thymic abnormalities. These findings suggest that thymic abnormalities may serve as potential markers of disease progression and could influence clinical management strategies, including the consideration for thymectomy in severe cases.